Field study evolution on a porous asphalt mixture pavement containing ladle furnace slag - Marta Skaf; A.B. Espinosa; V. Ortega-López; V. Revilla-Cuesta; J.M. Manso (Case Studies in Construction Materials)
A three-year study tracking the performance of a novel, environmentally sustainable pavement, a Porous Asphalt (PA) mix incorporating Ladle Furnace (LF) slag, is presented in this paper. A thin layer of this material was applied over an existing pavement, in a pilot project of approximately 300 m2. The main results of the research refer to the successful scaling up from laboratory design to full-scale manufacturing, laying, and compaction, validating the use of up to 10 % LF slag in the mixture. The pavement demonstrated satisfactory durability in terms of resistance to abrasion, accelerated aging, frost, and humidity. The leaching behavior of the mixture remained well below regulatory limits. Over the three-year monitoring period, skid resistance remained stable, consistently exceeding 70 BPN (British Pendulum Number), while the permeability coefficient in dust-protected areas was maintained at 10⁻¹ cm/s. Moreover, visual inspections revealed no surface deficiencies throughout the study.